The articles by Gramsci published in English in International Press Correspondence - Boothman, Derek; Gramsci, Antonio (International Gramsci Journal, 2023)
The articles included here represent most of what Gramsci published in the Comintern journal International Press Correspondence, under his own name or one of his pseudonyms of the period, G. (sometimes Giovanni) Masci. 1 In much of this period Inprecorr was coming out more or less twice a week, with articles from all parts of the world, including from Russia, with articles written by the various Party and Union leaders. Even during the period of great polemics which basically started just before Lenin’s death and carried on over the whole of this period, the Inprecorr in its various languages of publication, carried articles giving all points of view written by all the participants in the controversies. This was true both of the Russian communists, so the Trotsky controversy was given full airing from both sides, and of those involved in other debates outside Russia. In Italy, for example, it was not only the extreme left of Amadeo Bordiga that was present in the Party, and that found space in the pages of Inprecorr, but also the right of Angelo Tasca – one of the Turin Ordine Nuovo group and, up to near the end of Gramsci’s stay in Moscow, one who had the ear of the Comintern leadership. And another on the right was Antonio Graziadei, an economist judged to hold a “revisionist” stance, whose views were expressed fully both in Inprecorr and in book International Press Correspondence came out regularly in Russian, French, German and English (with the abbreviation Inprecorr), and sometimes, it seems, also in a Spanish edition. The period of the articles published here ranges from 1922, up through Gramsci’s half- year stay in Vienna (December 1923 to May 1924), and on to the last period when, after his election as a parliamentary deputy, he was able to return to Italy on the basis of parliamentary immunity. With his new status as a deputy he could in theory evade the warrant that had been put out for his arrest in February 1923.